Gas gain stabilisation in the ATLAS TRT detector. (29th April 2016) - Mindur, B.; Åkesson, T.P.A.; Anghinolfi, F.; Antonov, A.; Arslan, O.; Baker, O.K.; Banas, E.; Bault, C.; Beddall, A.J.; Bendotti, J.; Benjamin, D.P.; Bertelsen, H.; et al.
Abstract: The ATLAS (one of two general purpose detectors at the LHC) Transition Radiation Tracker (TRT) is the outermost of the three tracking subsystems of the ATLAS Inner Detector. It is a large straw-based detector and contains about 350, 000 electronics channels. The performance of the TRT as tracking and particularly particle identification detector strongly depends on stability of the operation parameters with most important parameter being the gas gain which must be kept constant across the detector volume. The gas gain in the straws can vary significantly with atmospheric pressure, temperature, and gas mixture composition changes. This paper presents a concept of the gas gain stabilisation in the TRT and describes in detail the Gas Gain Stabilisation System (GGSS) integrated into the Detector Control System (DCS). Operation stability of the GGSS during Run-1 is demonstrated.